L₀-regularization based material design for hexahedral mesh models - Li, Haoxiang (2022)
The deformation behavior of a deformable part depends on its underlying material. Properly distributing heterogeneous elastic materials over an object is important in part design and becomes an active research topic in computer aided design and graphics. This paper considers the problem of how to design heterogeneous elastic materials over a hexahedral mesh model that commonly appears in computer-aided design and engineering applications. Existing approaches to solving the problem typically apply L2 regularization that is good for smoothly distributed material. Considering that many real-world objects likely have sparse material distribution, we propose an optimization formulation with a carefully designed objective function and L0 regularization. An iterative algorithm is presented to solve the L0-optimization problem. The L0 regularization encourages sparsity of the output material distribution, which may facilitate some approaches for digital material design in multi-material additive manufacturing. The experimental results show that the proposed method can output material distribution to produce the desired deformation behavior.